Content and composition of essential oil of four Origanum vulgare L. accessions under reduced and normal light intensity conditions - Shafiee-Hajiabad, Marzieh; Novak, Johannes; Honermeier, Bernd; Justus Liebig University Giessen (My University, 2016)
The variation in the chemical composition and content of the essential oil was examined in four Origanum vulgare accessions (Ov): 1- Origanum vulgare L. ssp. vulgare (=Ovu), 2- Origanum vulgare L. ssp. hirtum (Link) letswaart (=Ohi), 3- Origanum vulgare L. ssp. viride (Boiss.) Hayek (=Ovi) and 4- Origanum vulgare L. ssp. viride (Boiss.) Hayek × O. majorana L. (=Oxm), growing under reduced (26%) and normal light intensity. Altogether, 64 compounds representing 98.95% of the total oil were identified. Reduced light had a minor effect on the composition of essential oil. It decreased the content of p-cymene in Ohi and increased the sabinene content in Oxm herb samples. The essential oil of Ovu in both samples was mainly composed of trans-sabinene hydrate, ß-caryophellene and germacrene D. The major components of essential oil of Ohi were thymol and carvacrol followed by gamma-terpinene and p-cymene. Herb samples had a considerably higher amount of essential oil than leaf samples. In herb extracts of Ovi, cymyl compounds such as p-cymene, thymol and gamma-terpinene were dominant. Oxm was characterized by several monoterpenes with low concentrations including gamma-terpinene, sabinene cis-b-ocimene and carvacrol methyl ether. The results of the current study suggest a chemical toleration of the evaluated accessions to the applied light reduction. Furthermore, a full investigation of essential oil profiles of Origanum vulgare accessions is presented.
Keywords: ddc:630